Depletion of ε-COP in the COPI Vesicular Coat Reduces Cleistothecium Production in Aspergillus nidulans - Kang, Eun-Hye (Mycobiology, 2015)
We have previously isolated ε-COP, the α-COP interactor in COPI of Aspergillus nidulans, by yeast two-hybrid screening. To understand the function of ε-COP, the aneA(+) gene for ε-COP/AneA was deleted by homologous recombination using a gene-specific disruption cassette. Deletion of the ε-COP gene showed no detectable changes in vegetative growth or asexual development, but resulted in decrease in the production of the fruiting body, cleistothecium, under conditions favorable for sexual development. Unlike in the budding yeast Saccharomyces cerevisiae, in A. nidulans, over-expression of ε-COP did not rescue the thermo-sensitive growth defect of the α-COP mutant at 42℃. Together, these data show that ε-COP is not essential for viability, but it plays a role in fruiting body formation in A. nidulans.